Study Of The Application Garuda Pancasila Symbol on The Flags and Banners Ornaments of Indonesia Independence Day Celebration - Fransiska Rachel; A.M. Hermanto Laksana; Yuniarti Rahayu (Asosiasi Program Studi Desain Komunikasi Visual Indonesia (Asprodi DKV), 2021)
Approaching the Independence Day of the Republic Indonesia, the phenomenon of selling banners, flags and various other complementary decorations for Independence Day celebration arise. The interesting thing about this phenomenon is the emergence of a new phenomenon where the use of Garuda Pancasila symbol as decoration of aesthetic elements on banners and flag. However, the use of Garuda Pancasila symbol is often followed by other additional decorative elements that overlap or even change the original character of the symbol. This study aims to collect the application of Garuda Pancasila logo and the decorations used, compile the phenomenology and analyze from the point of view of visual communication design, especially semiotics which is based on visual, semantic, syntactic and pragmatic analysis. The final goal of this research is to provide input to the government to provide clear rules and Design Ethics on the proper and correct use or application of the Garuda Pancasila symbol.